2022
DOI: 10.3390/ijms23158113
|View full text |Cite
|
Sign up to set email alerts
|

Removal of MuRF1 Increases Muscle Mass in Nemaline Myopathy Models, but Does Not Provide Functional Benefits

Abstract: Nemaline myopathy (NM) is characterized by skeletal muscle weakness and atrophy. No curative treatments exist for this debilitating disease. NM is caused by mutations in proteins involved in thin-filament function, turnover, and maintenance. Mutations in nebulin, encoded by NEB, are the most common cause. Skeletal muscle atrophy is tightly linked to upregulation of MuRF1, an E3 ligase, that targets proteins for proteasome degradation. Here, we report a large increase in MuRF1 protein levels in both patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…No change in myostatin was observed in a mouse model of mild actin-based NM. Additionally, myostatin positively regulates the expression of MuRF1 and MAFbx [16,26] and last year, we found that MuRF1 protein levels are elevated in a limited number of patients and two animal models of NEM2 [48]. Collectively, current data from animal experiments and clinical trials indicate that myostatin inhibition increases muscle size in animals and humans, but improvements in muscle function are diseasedependent [49].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…No change in myostatin was observed in a mouse model of mild actin-based NM. Additionally, myostatin positively regulates the expression of MuRF1 and MAFbx [16,26] and last year, we found that MuRF1 protein levels are elevated in a limited number of patients and two animal models of NEM2 [48]. Collectively, current data from animal experiments and clinical trials indicate that myostatin inhibition increases muscle size in animals and humans, but improvements in muscle function are diseasedependent [49].…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies [20,24,48] have provided detailed descriptions of the intact muscle mechanic experiments. In brief, extensor digitorum longus (EDL) muscles were rapidly excised, and silk suture loops (USP 4-0) were tied to each tendon.…”
Section: Intact Muscle Mechanicsmentioning
confidence: 99%
“…[26][27][28][29][30][31] It has also been implicated in the regulation of thin filament length (TFL), as reduced levels of nebulin protein have been associated with shortened TFL in patients with NEB-related nemaline myopathy, as well as in nebulin-deficient mouse models, zebrafish, and chick skeletal myocytes. 30,[32][33][34][35][36][37][38][39] Despite investigating a number of therapeutic interventions including troponin activators such as Levosimendan, 40 CK-20066260, 30 dietary supplements 41 and myostatin inhibitors, 42,43 there are currently no effective therapies targeting the underlying pathological mechanisms for nebulinbased NEM (NEM2). It has been shown that Omecamtiv mecarbil (OM), a selective smallmolecule activator of cardiac myosin (MYH7) that was initially developed as a treatment for heart failure, 44,45 , increases submaximal force production in type I skeletal muscles of Neb cKO mouse model 46 and rat diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Despite investigating a number of therapeutic interventions including troponin activators such as Levosimendan, 40 CK-20066260, 30 dietary supplements 41 and myostatin inhibitors, 42,43 there are currently no effective therapies targeting the underlying pathological mechanisms for nebulin-based NEM (NEM2). It has been shown that Omecamtiv mecarbil (OM), a selective small-molecule activator of cardiac myosin ( MYH7) that was initially developed as a treatment for heart failure, 44,45 , increases submaximal force production in type I skeletal muscles of Neb cKO mouse model 46 and rat diaphragm.…”
Section: Introductionmentioning
confidence: 99%